Restricted T-Cell Repertoire in the Epicardial Adipose Tissue of Non-ST Segment Elevation Myocardial Infarction Patients - Pedicino, Daniela; Severino, Anna; Di Sante, Gabriele; De Rosa, Maria Cristina; Pirolli, Davide; Vinci, Ramona; Pazzano, Vincenzo; Giglio, Ada F.; Trotta, Francesco; Russo, Giulio; Ruggio, Aureliano; Pisano, Eugenia; et al. (Frontiers in Immunology, 2022)
Aims Human epicardial adipose tissue, a dynamic source of multiple bioactive factors, holds a close functional and anatomic relationship with the epicardial coronary arteries and communicates with the coronary artery wall through paracrine and vasocrine secretions. We explored the hypothesis that in patients with Non-ST segment Elevation Myocardial Infarction (NSTEMI) T-cell recruitment into epicardial adipose tissue (EAT) could be part of a specific antigen-driven response implicated in acute coronary syndrome onset and progression. Methods and Results We enrolled 32 NSTEMI patients and 34 chronic coronary syndrome (CCS) patients undergoing coronary artery bypass grafting (CABG), and 12 mitral valve disease (MVD) patients undergoing surgery. We performed EAT proteome profiling on pooled specimens from 3 NSTEMI and 3 CCS patients. We performed T-cell receptor (TCR) spectratyping and CDR3 sequencing in EAT and in peripheral blood mononuclear cells of 29 NSTEMI, 31 CCS and 12 MVD patients. We then used computational modeling studies to predict interactions of the TCR beta chain variable region (TRBV) and explore sequence alignments. The EAT proteome profiling displayed a higher content of pro-inflammatory molecules (CD31, CHI3L1, CRP, EMPRINN, ENG, IL-17, IL-33, MMP-9, MPO, NGAL, RBP-4, RETN, VDB) in NSTEMI as compared to CCS (p<0.0001). CDR3-beta spectratyping showed a TRBV21 enrichment in EAT of NSTEMI (12/29 patients; 41%) as compared with CCS (1/31 patients; 3%) and MVD (none) (ANOVA for trend P<0.001). Of note, 11/12 (92%) NSTEMI patients with TRBV21 perturbation were at their first manifestation of ACS. Four patients with the first event shared a distinctive TRBV21-CDR3-sequence of 178b length and 2/4 were carriers of the human leukocyte antigen (HLA)-A*03:01 allele. A 3D analysis predicted the most likely epitope able to bind HLA-A3*01 and to interact with the TRBV21-CDR3-sequence of 178b length, while the alignment results were consistent with microbial DNA sequences. Conclusions Our study revealed a unique immune signature of the epicardial adipose tissue, which led to a 3D modeling of the TCRBV/peptide/HLA-A3 complex, in acute coronary syndrome patients at their first event, paving the way for epitope-driven therapeutic strategies.